How do intermediary organizations affect cultivated land conservation in China: the mediating role of land tenure stability - Cai, Jian; Chen, Jiating; Wu, Runmin; Omar, Rosmini; Ning, Binyao (Frontiers in Sustainable Food Systems, 2025)
Economic pressure frequently prompts farmers in developing regions to prioritize immediate financial returns over long-term land conservation. This study examines how land intermediary organizations affect Chinese farmers’ willingness to conserve cultivated land. Using bounded rationality and property rights theories, we conducted quantitative research involving 564 farmers across five provinces in mainland China. The results show that intermediary organizations improve farmers’ willingness to conserve land, mediated by land tenure stability. Notably, both human capital (education level) and social capital (village cadre status) negatively moderated the impact of intermediary organizations’ involvement in farmers’ willingness to conserve cultivated land. The results of this study indicate the necessity of improving land conservation practices, considering the role of institutional support and individual characteristics of farmers. In terms of policy implications, there is a need to adapt intermediary services to align with the capital levels of farmers, enhance the security of land-use rights by streamlining registration procedures, and implement targeted information systems and incentive schemes. Limitations of this study include its cross-sectional design and potential regional variations.